(untitled) (Journal of Surgical Sciences, 2019)
Pica is a worldwide problem that has no barriers of age, race, gender or geography. Picamay be benign or it may have life threatening consequences. We report here a case of 28-year-old male, electrician apparently psychologically sound got admitted with complaints ofpersistent pain in upper abdomen and vomiting with history of ingestion of dinner fork andtooth brush. Laparotomy was done to remove the foreign bodies and later referred topsychiatry department where he was diagnosed as an adult onset pica due to schizophrenia.Pica in elderly age group is relatively uncommon, and it rarely has an adult onset. Journal of Surgical Sciences (2016) Vol. 20 (2) :62-64